PENERAPAN STATISTICAL QUALITY CONTROL DALAM PENGENDALIAN MUTU PRODUKSI SNACK EGGROLL - Anggraeni, Rila; Izza, Navisah Ainul (Jurnal Kewirausahaan dan Inovasi, 2022)
The processing industry is an industry that plays a major role in Indonesia's economic growth where the food and beverage sub-sector is the most dominating. Intense competition in the food industry encourages businesses to continue to innovate and control quality by reducing defects. Barin Food is an SME in Malang producing processed food distinctive to Malang; eggroll is one of its featured products. In the first quarter of 2022, it is recorded that 6831 pieces of vanilla eggroll were broken. The company has not used any instrument to control product quality. The goal of this study is to apply Statistical Quality Control method to minimize broken product in the company using histogram, Control Chart, and Fishbone Chart. The results of the analyses show that the company needs to suppress the number of broken products. The cause of the flaws is divided into four: human, machine, material, and environment. The result of the SQC analysis suggest the renewal of production machines.